2012
DOI: 10.1080/08974454.2012.687966
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing the Matron: The Continued Importance of Gendered Images and Division of Labor in Modern Policing

Abstract: The current research examines the workplace images and responsibilities of female police officers in 3 departments. Ethnographic interviews with 28 officers in 3 midwestern communities indicate that women in law enforcement are still viewed through a gendered lens, which shapes relations with fellow officers and the community. Images of female officers correspond to their early role in law enforcement as matrons charged with the care of female offenders and juvenile delinquents. Results indicate that female of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For example, an observational study of one rural southeastern police academy found that during training, female recruits were consistently treated by male recruits and instructors as outsiders, were denigrated and objectified as sexual objects, and were told that powerful women would be resisted and not taken seriously should they rise up through the ranks (Prokos & Padavic, 2002). Beyond the academy (i.e., field training and later career paths), the perception of female officers as subordinated to a "matron" role may persist and manifest as an expectation that female officers will take devalued positions working with juveniles and domestic violence cases, as seen in a study of three departments (Kurtz et al, 2012).…”
Section: Masculine Police Subculturementioning
confidence: 99%
“…For example, an observational study of one rural southeastern police academy found that during training, female recruits were consistently treated by male recruits and instructors as outsiders, were denigrated and objectified as sexual objects, and were told that powerful women would be resisted and not taken seriously should they rise up through the ranks (Prokos & Padavic, 2002). Beyond the academy (i.e., field training and later career paths), the perception of female officers as subordinated to a "matron" role may persist and manifest as an expectation that female officers will take devalued positions working with juveniles and domestic violence cases, as seen in a study of three departments (Kurtz et al, 2012).…”
Section: Masculine Police Subculturementioning
confidence: 99%
“…However, women are perceived to be weak, unable to fulfill job requirements, and a physical liability for the organization (Brown, 1998; Martin, 1999; Schulz, 2009; Wadman & Allison, 2004). This recurring image fosters a cultural tradition that characterizes women as physically inferior, despite the fact that physical altercations are infrequent in modern policing (Kurtz, Linneman, & Williams, 2012). The incursion of women into the police culture has the capacity to alter these norms, values, and customs and hence is met with great resistance (Hughes, 2011; Rabe-Hemp, 2008).…”
Section: Law Enforcement Culturementioning
confidence: 99%
“…Given that managerial posts are overwhelming male dominated, the performance appraisal system can be ripe with gender bias and continue to adversely impact women (Caceres-Rodriguez, 2011). Despite executive and legislative efforts in the past 50 years to remove systematic barriers, women in law enforcement remain undervalued by a male-dominated culture and the pervasive negative attitudes of male colleagues and supervisors (Carlan & McMullan, 2009; Dodge, Valcore, & Klinger, 2010; Kurtz, Linnemann, & Williams, 2012; Morash & Haarr, 2012; Swan, 2016; Yu, 2015).…”
Section: Glass Ceiling Representative Bureaucracy and Federal Law Ementioning
confidence: 99%